2000
DOI: 10.1590/s1516-89132000000200010
|View full text |Cite
|
Sign up to set email alerts
|

Feeding of Acestrorhynchus lacustris (Characidae): a post impoundment studies on Itaipu reservoir, upper Paraná River, PR

Abstract: With objective to know feeding spectrum of Acestrorhynchus lacustris (Reinhardt, 1874)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 9 publications
2
21
0
2
Order By: Relevance
“…Bennemann et al (1996) have observed a piscivorous feeding habit for A. lacustris. The same was observed by Hahn et al (2000), Gomes and Verani (2003) and Pompeu and Godinho (2003). They all observed that fish small individuals of A. altiparanae were commonly found and they should be potentially ingested by A. lacustris.…”
Section: The State Areasupporting
confidence: 82%
See 3 more Smart Citations
“…Bennemann et al (1996) have observed a piscivorous feeding habit for A. lacustris. The same was observed by Hahn et al (2000), Gomes and Verani (2003) and Pompeu and Godinho (2003). They all observed that fish small individuals of A. altiparanae were commonly found and they should be potentially ingested by A. lacustris.…”
Section: The State Areasupporting
confidence: 82%
“…In other aquatic systems (Almeida et al, 1997;Hahn et al, 2000;Gomes and Verani, 2003;Pompeu and Godinho, 2003), consisting of larger rivers than the stream where this study was carried out. A study in such a small stream over a whole year more clearly shows distinctions, as distinct seasons also cause a considerable difference of the water level, which may influence the food availability for this species.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hahn et al (2000) found only fish in the stomachs of individuals of Acestrorhyncus lacustris over 10 cm long in the Itaipu Reservoir. Araújo et al (2005) observed a similar situation, in which Oligosarcus hepsetus larger than 19 cm fed principally on fish, in contrast to smaller individuals which fed principally on insects.…”
Section: Discussionmentioning
confidence: 91%